Immunological characteristics of MAV/06 strain of varicella-zoster virus vaccine in an animal model - Duckhyang Shin; Younchul Shin; Eunmi Kim; Hyojung Nam; Haiyan Nan; Jaewoo Lee (BMC Immunology, 2022)
Abstract Background Varicella-zoster virus (VZV) is a pathogen that causes chickenpox and shingles in humans. Different types of the varicella vaccines derived from the Oka and MAV/06 strains are commercially available worldwide. Although the MAV/06 vaccine was introduced in 1990s, little was known about immunological characteristics. Results Here, we evaluated B and T cell immune response in animals inoculated with the Oka and MAV/06 vaccines as well as a new formulation of the MAV/06 vaccine. A variety of test methods were applied to evaluate T and B cell immune response. Plaque reduction neutralization test (PRNT) and fluorescent antibody to membrane antigen (FAMA) assay were conducted to measure the MAV/06 vaccine-induced antibody activity against various VZVs. Glycoprotein enzyme-linked immunosorbent assay (gpELISA) was used to compare the degree of the antibody responses induced by the two available commercial VZV vaccines and the MAV/06 vaccine. Interferon-gamma enzyme-linked immunosorbent spot (IFN-γ ELISpot) assays and cytokine bead array (CBA) assays were conducted to investigate T cell immune responses. Antibodies induced by MAV/06 vaccination showed immunogenicity against a variety of varicella-zoster virus and cross-reactivity among the virus clades. Conclusions It is indicating the similarity of the antibody responses induced by commercial varicella vaccines and the MAV/06 vaccine. Moreover, VZV-specific T cell immune response from MAV/06 vaccination was increased via Th1 cell response. MAV/06 varicella vaccine induced both humoral and cellular immune response via Th1 cell mediated response.